Non‐Flammable and Highly Concentrated Carbonate Ester‐Free Electrolyte Solutions for 5 V‐Class Positive Electrodes in Lithium‐Ion Batteries. Issue 11 (7th May 2021) - Doi, Takayuki; Taccori, Romain Jun; Fujii, Ryo; Nagashima, Tsuyoshi; Endo, Takatsugu; Kimura, Yoshifumi; Inaba, Minoru
Abstract: Non‐flammable and highly concentrated electrolyte solutions were designed using tris(2, 2, 2‐trifluoroethyl) phosphate (TFEP) as a main solvent toward a radical improvement in the safety and energy density of lithium‐ion batteries. Unlike conventional carbonate ester‐based solutions, simple TFEP‐based electrolyte solutions were not intrinsically compatible with 5 V‐class LiNi0.5 Mn1.5 O4 positive electrodes, even at high concentrations. Based on the degradation mechanism that was analyzed by Raman spectroscopy, scanning electron microscopy/energy dispersive X‐ray spectroscopy, and X‐ray photoelectron spectroscopy, a fluorinated diluent of methyl 3, 3, 3‐trifluoropropionate (FMP) was introduced to suppress the decomposition of LiBF4 and TFEP at high potentials. A nearly saturated LiBF4 /TFEP+FMP electrolyte solution with a specific composition improved the charge and discharge performance of a LiNi0.5 Mn1.5 O4 electrode, and the solution structure was studied by pulsed‐field‐gradient NMR spectroscopy. Abstract : Drift compatible : Non‐flammable tris(2, 2, 2‐trifluoroethyl) phosphate (TFEP)‐based electrolyte solutions containing LiBF4 are not intrinsically compatible with 5 V‐class LiNi0.5 Mn1.5 O4 positive electrodes, even at very high concentrations. The charge/discharge performance decreases as the concentration increases. The introduction of a fluorinated diluent effectively stabilizes the electrolyte solution at high potentials, and as a result the cycle performance improves remarkably.